Mosquito Control Agents Derived From Petroleum Hydrocarbons. I. Laboratory Effectiveness. Issue 2 (24th September 2014) - Micks, D. W.; Chambers, G.; Jennings, J.; Rehmet, A.
Abstract : One hundred ten hydrocarbons derived from petroleum were evaluated against the eggs, larvae, and pupae of the southern house mosquito, Culex pipiens quinquefasciatus Say, ( =C. fatigans (Wiedemann), and the yellow-fever mosquito, Aedes aegypti (L.), using 6 different test procedures. Of the test materials, 56 ranged from 2 to 8 times as effective as the no. 2 diesel fuel standard against larvae, 25 produced 100% mortality in C. fatigans pupae when applied at the rate of 5 gallons per acre, 20 exhibited a greater residual effect than the standard, and 25 were faster acting than the control. The test materials were generally more effective against the aquatic stages of C. p. quinquefasciatus than those of A. aegypti . The 2 test procedures involving the water surface application of oils to containers of larvae and pupae were found to be the most satisfactory for routine evaluation of the materials.